Target and Background Signatures III 2017
DOI: 10.1117/12.2277190
|View full text |Cite
|
Sign up to set email alerts
|

Automatic X-ray image segmentation and clustering for threat detection

Abstract: Firearms currently pose a known risk at the borders. The enormous number of X-ray images from parcels, luggage and freight coming into each country via rail, aviation and maritime presents a continual challenge to screening officers. To further improve UK capability and aid officers in their search for firearms we suggest an automated object segmentation and clustering architecture to focus officers' attentions to high-risk threat objects. Our proposal utilizes dual-view single/ dual-energy 2D X-ray imagery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The study used dual-view single/dual-energy 2D X-ray imagery and a triplelayered processing scheme based on the atomic number of the contents of the luggage. It combined radiology, image processing, and computer vision concepts [6]. The study supports the research as it aims to improve the current method of detecting high-risk objects and enhancing the results [6].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The study used dual-view single/dual-energy 2D X-ray imagery and a triplelayered processing scheme based on the atomic number of the contents of the luggage. It combined radiology, image processing, and computer vision concepts [6]. The study supports the research as it aims to improve the current method of detecting high-risk objects and enhancing the results [6].…”
Section: Introductionmentioning
confidence: 59%
“…The SURF algorithm can achieve this by using color invariant transformations, information entropy theory, and a set of constraint conditions to improve feature point identification and matching. In line with the study, a study from 2017 suggested using an automated object segmentation and clustering architecture to detect high-risk threat objects in the UK [6]. The study used dual-view single/dual-energy 2D X-ray imagery and a triplelayered processing scheme based on the atomic number of the contents of the luggage.…”
Section: Introductionmentioning
confidence: 95%
“…Instead of using shape information, some approaches utilises chemical (attenuation) proporties [28] and high atomic numbers [55]. Nearest Neighbour Distance Ratio [114] on SURF [100] features computed on regions disconnected with morphological operations achieves promising results (RMS error: 1.15 on 23 X-ray images).…”
Section: Object Segmentationmentioning
confidence: 99%
“…However, the deep learning model has high computational complexity and limited recognition accuracy, which may lead to misjudgment. There are other nondestructive testing methods such as magnetic particle testing [5], ray detection [6], and ultrasonic testing [7]. Ultrasonic testing is widely used among them, as its accuracy is high and it is easily operated.…”
Section: Introductionmentioning
confidence: 99%